PEMEROLEHAN BAHASA MELALUI MEMBACA PERMULAAN PADA TINGKAT SEMANTIC MEMORY ANAK SEKOLAH DASAR - Jupitasari, Mellisa; Sulissusiawan, Ahadi; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research aims to describe the language acquisition of children on the cognition aspects of the ability to read the beginning of primary school children based on the level of semantic memory (SM) or the process of understanding the sentence. This study used qualitative descriptive method and used psycholinguistic approach to analyze the language acquisition of child based on the reading ability of elementary school students based on semantic memory (SM) level. This research was conducted at State Elementary School 31 South of Pontianak. The data source of this research is children aged 6-8 years. Based on the research that has been done about the language acquisition of child on the cognition aspect of early childhood reading ability based on the level of semantic memory (SM) or the process of understanding the sentence, only 1 children can understand the reading content of the given indicator. The rest there are 16 children who only understand some of the reading so as to answer incomplete indicators and 8 children who do not understand the contents of the reading so that they can not answer the question of the indicator incorrectly. The importance of the experience gained in the child's surrounding environment is one of the factors that helps language acquisition in particular against the knowledge of reading. Therefore, parents should pay more attention to the process in order to read the language acquisition process can be improved.Â Keywords: Language Acquisition, Beginning Reading, Semantic Memory, Primary School Children,PsycholingisticÂ